Classification of conformal carroll algebras - Hamid Afshar; Xavier Bekaert; Mojtaba Najafizadeh (Journal of High Energy Physics)
Abstract We classify a one-parameter family, confcar r z d + 1 $$ \mathfrak{confcar}{\mathfrak{r}}_z\left(d+1\right) $$ , of conformal extensions of the Carroll algebra in arbitrary dimension with z being the anisotropic scaling exponent. We further obtain their infinite-dimensional extensions, confcarr ~ z d + 1 $$ {\overset{\sim }{\mathfrak{confcarr}}}_z\left(d+1\right) $$ , and discuss their corresponding finite-dimensional truncated subalgebras when the scaling exponent is integer or half-integer. For all these conformal extensions, we also constrain the 2-point and 3-point correlation functions with electric and/or magnetic features.